2009
DOI: 10.1152/ajpcell.00415.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroid hormone on mitochondrial properties and oxidative stress in cells from patients with mtDNA defects

Abstract: Menzies KJ, Robinson BH, Hood DA. Effect of thyroid hormone on mitochondrial properties and oxidative stress in cells from patients with mtDNA defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 53 publications
3
20
0
1
Order By: Relevance
“…As a consequence of TH stimulation, increasing levels of mitochondrial activities of bio-energetic enzymes can subsequently enhance ATP generation [42]. According to our results, phosphine poisoning caused a 50% decline in cellular ATP reserve.…”
Section: Accepted Manuscriptsupporting
confidence: 52%
“…As a consequence of TH stimulation, increasing levels of mitochondrial activities of bio-energetic enzymes can subsequently enhance ATP generation [42]. According to our results, phosphine poisoning caused a 50% decline in cellular ATP reserve.…”
Section: Accepted Manuscriptsupporting
confidence: 52%
“…Columbano et al (16) reported that T3 stimulated the proliferation of hepatocytes in rat models of liver regeneration. T3 could reduce cellular oxidative stress, which may help attenuate reactive oxygen species (ROS)-mediated damage, along with improving mitochondrial function and energy status in cells with mitochondrial DNA defects (17). The NADH dehydrogenase flavoprotein 2 gene located on 18p11.22 encodes a component of mitochondrial complex 1.…”
Section: Ohkubo Et Almentioning
confidence: 99%
“…Available data showed that T3 could reduce oxidative stress and weaken the damage mediated by reactive oxidative species (ROS). 9 Antioxidant treatment is regarded as a potential effective measure to attenuate the oxidative stress. Pyrrolidine dithiocarbamate (PDTC), a metal chelator and antioxidant, is a specific inhibitor of NF-kB.…”
Section: Introductionmentioning
confidence: 99%